Ab.: Abl: en latín clásico: Caracterización funcional - Hernández Cabrera, Tomás (1998)
In this paper the author shows that in classical latin the ab... abl. preposition is a formal mark of the following four Semantics Functions (SF): Source, Timefrom-which, Cause and Agent.
Keywords: Sintaxis; Gramática; Lengua latina